2009
DOI: 10.1111/j.1365-313x.2009.03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and integration of thylakoid protein translocase subunit cpTatC

Abstract: SUMMARYThylakoid membranes have a unique complement of proteins, most of which are nuclear encoded synthesized in the cytosol, imported into the stroma and translocated into thylakoid membranes by specific thylakoid translocases. Known thylakoid translocases contain core multi-spanning, membrane-integrated subunits that are also nuclear-encoded and imported into chloroplasts before being integrated into thylakoid membranes. Thylakoid translocases play a central role in determining the composition of thylakoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Only slight reductions of the outer envelope protein TOC75 were observed. In contrast, the abundance of most of these proteins, with the exception of SCY1, was unaffected in SCY1-RNAi seedlings, consistent in part with previous results (Martin et al, 2009). These results suggest that the loss of SCY2 creates a different and more global effect on chloroplast biogenesis in developing seedlings than loss of SCY1.…”
Section: Inducible Down-regulation Of Scy2 In Arabidopsissupporting
confidence: 77%
See 2 more Smart Citations
“…Only slight reductions of the outer envelope protein TOC75 were observed. In contrast, the abundance of most of these proteins, with the exception of SCY1, was unaffected in SCY1-RNAi seedlings, consistent in part with previous results (Martin et al, 2009). These results suggest that the loss of SCY2 creates a different and more global effect on chloroplast biogenesis in developing seedlings than loss of SCY1.…”
Section: Inducible Down-regulation Of Scy2 In Arabidopsissupporting
confidence: 77%
“…This appears to be due to a breakdown of RNAi, as SCY1 null mutants are stably and uniformly chlorotic (Martin et al, 2009;Skalitzky et al, 2011). qRT-PCR analysis confirmed that both SCY1 and SCY2 transcripts had returned to wildtype levels in the green true leaves (Martin, 2010).…”
Section: Inducible Down-regulation Of Scy2 In Arabidopsismentioning
confidence: 72%
See 1 more Smart Citation
“…Thylakoids are thought to initiate through the budding or invagination of the inner envelope membrane (for discussion, see von Wettstein, 2001;Vothknecht and Westhoff, 2001), and translocases that mediate the expansion and population of proteins of the system may themselves need to be initially inserted in the envelope (for discussion, see Cline, 2003). This has been proposed for the cpTatC subunit based on experimental observations that are inconsistent with integration by any of the known thylakoid translocase systems (Martin et al, 2009). The cpTat complex assembles in scy1 and alb3 mutants, and biochemical inhibitors of cpTat and SRP were without effect on cpTatC localization.…”
Section: Role Of Secementioning
confidence: 99%
“…In bacteria, the homologous subunits are cotranslationally integrated by the Sec machinery (for discussion, see Martin et al, 2009). A recent study of the biogenesis of cpTatC ruled out involvement of the thylakoid Tat, Sec, and SRP systems as well as the YidC homolog Alb3 (Martin et al, 2009). Because cpTatC is not integrated into isolated thylakoids, the spontaneous pathway is also not involved.…”
mentioning
confidence: 99%